KONTRIBUSI PENDAPATAN INDUSTRI KUNYIT BUBUK TERHADAP PENDAPATAN KELUARGA DI DESA GUNUNG SILANU KECAMATAN BANGKALA KABUPATEN JENEPONTO - Irdayanti, Dian Frida (LaGeografia, 2019)
This study aims to determine : Contribution of turmeric powder industry business income to family income in Gunung Silanu Village. The population of this study as all the turmeric powder industry in Gunung Silanu Village which amout to 1 unit. The target in this study was 19 workers and an industrial owner of turmeric powder in Gunung Silanu Village. Data collection is done by using observation, interview, and documentation technique. The data is analyzed quantitatively ? qualitatively. The result of this study indicate that : The contribution of the turmeric powder industry business income to the income of the workforce family is included in the medium category with a percentage of 21,76 percent, which proves that as much as 78,04 percent of the family income contribution to labor is obtained from outside the industrial business.